Studi Komparasi Ahli Waris Pengganti (Plaatsvervulling) Dalam Perspektif KUH Perdata dan Kompilasi Hukum Islam - Muhammad; Syahrial Ahmad; Abdul Wahid Bagoes Timor Ali Ramdhan (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2023)
According to Pasal 185 of the Compilation of Islamic Law, a feeling of justice serves as the basis for institutionalizing alternative inheritance. In contrast, KUH Perdata includes clauses addressing replacement and replacement heirs (plaatsverfuling). Due to the continued application of customary law, Islamic law, and western law, inheritance law in Indonesia is still generally pluralistic. However, KUH Perdata and KHI are those pertaining to substitute heirs. Therefore, the authors are motivated to compare alternative heirs from the viewpoints of KUH Perdata and KHI. The author's preparation for the piece includes qualitative research with descriptive analytic techniques. The three stages of the data analysis process—description, formulation, and interpretation—are used in comparison analysis. According to the study's findings, if one heir dies before another heir, the child of the heir is then entitled to take the place of his father, in accordance with KHI and KUH Perdata of inheritance law. There are differences in the amount of the accepted heir's share; for example, KUH Perdata receives an equal share to the replacement, unlike KHI, which is not always the same as the replacement and does not exceed the share of equal heirs, and may even be reduced based on the replacement heir's sex. Additionally, KUH Perdata differs in that they enter information to determine the heirs. Keywords: Substitute heirs, KUH Perdata, KHI